Assessment of functional outcomes, level of fatigue, and risk of sarcopenia in COVID-19 patients at discharge: A cross sectional study - Nair, Nithin Ravindran; Nair, Shruti Prabhakaran; Panhale, Vrushali Prashant; Ravi, Ammarah Imtiaz; Jangid, Khushboo Sitaram; Kadam, Sameer Sudhir Chandra (International Journal Of Community Medicine And Public Health, 2024)
Background: There is emerging evidence with regards to reduced physical performance in patients recovering from COVID- 19 at time of hospital discharge. Assessing various functional parameters at discharge would shed light on the multi-system affection that could be helpful in formulating rehabilitation goals for the patient. Objectives of the study were to assess the physical performance, functional capacity, muscular strength, level of fatigue, and risk of sarcopenia in COVID-19 patients at discharge using short physical performance battery test, 1 minute sit to stand test, grip strength, fatigue assessment scale, SARC-CalF Scale respectively. Methods: This cross-sectional study comprised of 42 patients diagnosed with COVID-19 recruited from a tertiary care hospital. Demographic details and clinical variables were documented. Participants were assessed for physical performance, muscular strength, level of fatigue, functional capacity, and risk of sarcopenia. Data was analyzed using SPSS version 24. Results: The study comprised of 42 participants including 71.43% males (N=30) and 28.57% females (N=12) having mean age of 49.86±15.83 years. Findings of the assessed parameters were as follows: SPPB=7.57±2.84, 1 MSST=13.17±5.79 repetitions, grip strength=19.44±8.38 kg, FAS=19.79±10.83, SARC-CalF score=5.19±4.83. There was a weak positive correlation found between CT severity score and level of fatigue (r=0.325, p=0.036). Conclusions: This study provides a descriptive information about the functional outcomes of COVID -19 patients at discharge which can further be utilized for development of a tailor-made exercise program.